Efficacy of anti-TNF alpha in severe and/or refractory Behçet's disease: Multicenter study of 124 patients. (August 2015) - Vallet, H.; Riviere, S.; Sanna, A.; Deroux, A.; Moulis, G.; Addimanda, O.; Salvarani, C.; Lambert, M.; Bielefeld, P.; Seve, P.; Sibilia, J.; Pasquali, Jl; et al.
Abstract: Objective: To report the efficacy and safety of anti-TNF agents in patients with severe and/or refractory manifestations of Behçet's disease (BD). Methods: We performed a multicenter study of main characteristics and outcomes of anti-TNF alpha treatments [mainly infliximab (62%), and adalimumab (30%)] in 124 BD patients [48% of men; median age of 33.5 (28–40) years]. Results: Overall response (i.e. complete and partial) rate was 90.4%. Clinical responses were observed in 96.3%, 88%, 70%, 77.8%, 92.3% and 66.7% of patients with severe and/or refractory ocular, mucocutaneous, joint, gastro-intestinal manifestations, central nervous system manifestations and cardiovascular manifestations, respectively. No significant difference was found with respect to the efficacy of anti-TNF used as monotherapy or in association with an immunosuppressive agent. The incidence of BD flares/patient/year was significantly lower during anti-TNF treatment (0.2 ± 0.5 vs 1.7 ± 2.4 before the use of anti-TNF, p < 0.0001). The prednisone dose was significantly reduced at 6 and 12 months (p < 0.0001). In multivariate analysis, retinal vasculitis was negatively associated with complete response to anti-TNF (OR = 0.33 [0.12–0.89]; p = 0.03). The efficacy and relapse free survival were similar regardless of the type of anti-TNF agent used. After a median follow-up of 21 [7–36] months, side effects were reported in 28% of patients, including infections (16.3%) and hypersensitivity reactions (4.1%). Serious adverse events were reported in 13% of cases. Conclusion: Anti-TNF alpha therapy is efficient in all severe and refractory BD manifestations. Efficacy appears to be similar regardless of the anti-TNF agent used (infliximab or adalimumab). Highlights: Anti-TNF therapy is effective in all severe and/or refractory BD manifestations. Infliximab and Adalimumab seems to have similar efficacy and safety profile. Anti-TNF seems to have similar efficacy in monotherapy or in association with an IS agent.